Comparative analysis of the electronic and radiographic determination of root canal length of primary molars- an ex vivo study - Lucineide de Melo Santos Santos; José Ivo Limeira dos Reis (Universidade Estadual de Campinas, 2008)
Aim: ´To evaluate comparatively the radiographic and electronic root canal length determination in primary molars. Methods: 128 canals from 66 primary molars were selected. The root of each tooth was cut open on the occlusal face, and the real tooth length (RTL) was measured and the gold standard working length (WL) was determined by subtracting 1 mm from this measurement. The teeth were then placed in a plastic receptacle holding alginate and saline for the electronic determination of the root length using a Root ZX apex locator. The radiographic determination of the WL was obtained by subtracting 1 mm from the measurement highest cusp to the root apex appearing in the radiography. The data were analyzed statistically by the Chi-square test at a 5% significance level. Results: There was statistically significant difference (p<0.05) between each tested method and the gold standard. The Root ZX apex locator and the radiographic method presented satisfactory results in 75.78% and 54.68% of the cases, respectively. Conclusions: The Root ZX apex locator is a reliable method to determine the WL of primary teeth, since it showed greater accuracy than the radiographic method.